Shape influence of β-MnO2 on catalytic activity in the oxygen reduction reaction in alkaline media - Cruz-Reyes, Iván; Félix-Navarro, Rosa María; Trujillo-Navarrete, Balter (Pädi Boletín Científico de Ciencias Básicas e Ingenierías del ICBI, 2025)
Rutile-phase β-ΜnO2 nanostructures were produced using the hydrothermal method. The nanostructures were in the form of rods, and their hierarchical architecture to those resembling a dandelion flower were compared. The morphology was examined through scanning/transmission electron microscopy (SEM/TEM), the Rietveld refinement technique, and surface area analysis, while the oxidation states were determined using X-ray Photoelectron Spectroscopy-Ultraviolet Photoelectron Spectroscopy (XPS-UPS). Both nanostructures were evaluated as catalysts for the oxygen reduction reaction (ORR) in alkaline environments. The results suggest that introducing shape increased the specific surface area and the Mn4+/Mn3+ ratio. This variation can be attributed to the microstructural changes. The ORR was facilitated by a four-electron mechanism, increasing current density. This enhancement was observed, as well as in rod-shaped and dandelion-shaped structures. Hydrogen peroxide (H2O2) production rates were determined using a rotating ring-disk electrode (RRDE), which was less than 20% in dandelion compared to nanorods. This study enhances our understanding of β-ΜnO2 catalysts and highlights their potential in the energy conversion.